Changes in stride pattern of elite women's 400 metres hurdles from 2019 to 2022: an analysis by performance level - Casal-García, Nerea; López-Del Amo, José Luis (Frontiers in Sports and Active Living, 2025)
IntroductionThe main objective of this study was to investigate the stride patterns of elite women's 400 m hurdles which have undergone significant evolution in recent years, resulting in a complete change in the stride patterns of the athletes.MethodsTwo hundred and fifty-five individual performances of all participants in the World Championships in Doha 2019 and Oregon 2022, the Tokyo 2020 Olympic Games and the 2022 European Championships were analysed based on video recordings taken during the competition. The entire sample was divided into 3 performance-level groups (higher performance, intermediate performance, and lower performance). Correlation analysis, analysis of variance (Kruskall-Wallis) and linear multiple regression were performed.Results and discussionA total of 18 stride patterns have been identified, of which the most used by the highest performing athletes (58%) was the n + 1 pattern (consisting of adding a step between hurdle's intervals) maintaining 15 steps up to the 8th hurdle and then switching to 16 steps between hurdles 8th and 10th. In contrast, the majority of LP athletes used an n + 1 + 1 strategy, transitioning from 15 to 16 steps between the 5th and 6th hurdles (59%) and further increasing to 17 steps between hurdles 7th and 10th. Moreover, high-performance athletes take fewer strides during the race, with significant differences observed across all race intervals, particularly in the second half of the race. The number of steps between hurdles 8 and 9 predicted 78% of the ΔR2 of the athlete's total number of steps during the race, highlighting the importance of stride pattern and its changes during the final phase of the race.